PARP-1 Variant Rs1136410 Confers Protection against Coronary Artery Disease in a Chinese Han Population: A Two-Stage Case-Control Study Involving 5643 Subjects - Wang, Xue-bin; Cui, Ning-hua; Zhang, Shuai; Guo, Shu-ren; Liu, Ze-jin; Ming, Liang (Frontiers in Physiology, 2017)
Inhibition of poly(ADP-ribose) polymerase (PARP) may protect against coronary artery disease (CAD) in animal models, and rs1136410, a nonsynonymous single nucleotide polymorphism (SNP) in PARP-1, has a potential impact on PARP activities in vitro. This two-stage case-control study, involving 2803 CAD patients and 2840 controls, aimed to investigate the associations of PARP-1 rs1136410 with CAD development, lipid levels, PARP activities, 8-hydroxy-2'-dexyguanosine (8-OHdG), and interleukin (IL)-6 levels in a Chinese Han population. Assuming a recessive model, the variant genotype GG of SNP rs1136410 showed a significantly inverse association with CAD risk (adjusted odds ratio (OR) = 0.73, P < 0.001), left main coronary artery (LMCA) lesions (P = 0.003), vessel scores (P = 0.003), and modified Gensini scores (P < 0.001). There were significant correlations of SNP rs1136410 with higher levels of total cholesterol (TC) and lower levels of high-density lipoprotein cholesterol (HDL-c). In gene-environment interaction analyses, participants with the variant genotype GG, but without smoking habit, type 2 diabetes mellitus, and hyperlipidemia, conferred an 84% (P < 0.001) decreased risk of CAD. The genotype-phenotype correlation analyses further supported the functional roles of SNP rs1136410 in decreasing PARP activities and 8-OHdG levels. Taken together, our data suggest that SNP rs1136410 may confer protection against CAD through modulation of PARP activities and gene-environment interactions in a Chinese Han population.